Keracunan Organofosfat - Annisaul Ula; Surjit Singh (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Organophosphates are a group of compounds with toxic potential that inhibit cholinesterase, leading to the accumulation of acetylcholine at muscarinic, nicotinic receptors, and the central nervous system, which can result in death. Organophosphates are the most toxic insecticides compared to other types of pesticides and are often responsible for poisoning in humans. The symptoms of organophosphate poisoning vary widely. Each symptom depends largely on persistent acetylcholine stimulation or depression, followed by stimulation of the central and peripheral nervous systems. Early symptoms such as salivation, lacrimation, urination, and diarrhea (SLUD) occur in acute organophosphate poisoning due to stimulation of muscarinic receptors, leading to an increase in acetylcholine levels in the blood, eyes, and smooth muscles. Management of organophosphate poisoning involves stabilizing the patient, decontamination, and administering antidotes such as antimuscarinic agents, oximes, and anticonvulsants. Complications from organophosphate poisoning include respiratory failure, seizures, aspiration pneumonia, and even death. Postmortem examination of organophosphate poisoning may reveal cyanosis on the lips, fingertips, and nails, systemic or pulmonary congestion, dilation of the right heart, dark bluish-red livor mortis that forms more quickly, and a wider distribution of livor mortis due to high carbon dioxide levels.